Knowing what the patient wants: a hospital ethnography studying physician culture in shared decision making in the Netherlands - Didi Braat; Fedde Scheele; Laura Spinnewijn; Johanna Aarts; Sabine Verschuur; Trudie Gerrits (BMJ Open)
Objectives To study physician culture in relation to shared decision making (SDM) practice.Design Execution of a hospital ethnography, combined with interviews and a study of clinical guidelines. Ten-week observations by an insider (physician) and an outsider (student medical anthropology) observer. The use of French sociologist Bourdieu’s ’Theory of Practice’ and its description of habitus, field and capital, as a lens for analysing physician culture.Setting The gynaecological oncology department of a university hospital in the Netherlands. Observations were executed at meetings, as well as individual patient contacts.Participants Six gynaecological oncologists, three registrars and two specialised nurses. Nine of these professionals were also interviewed.Main outcome measures Common elements in physician habitus that influence the way SDM is being implemented.Results Three main elements of physician habitus were identified. First of all, the ‘emphasis on medical evidence’ in group meetings as well as in patient encounters. Second ’acting as a team’, which confronts the patient with the recommendations of a whole team of professionals. And lastly ‘knowing what the patient wants’, which describes how doctors act on what they think is best for patients instead of checking what patients actually want. Results were viewed in the light of how physicians deal with uncertainty by turning to medical evidence, as well as how the educational system stresses evidence-based medicine. Observations also highlighted the positive attitude doctors actually have towards SDM.Conclusions Certain features of physician culture hinder the correct implementation of SDM. Medical training and guidelines should put more emphasis on how to elicit patient perspective. Patient preferences should be addressed better in the patient workup, for example by giving them explicit attention first. This eventually could create a physician culture that is more helpful for SDM.